3 - Reinterpretation of “Traditional” Bodily Modifications by Young People in Contemporary Zimbabwe - Venganai, Hellen (Africa Development, 2018)
There is a rising critique against the dominant but negative Western discursive construction of ‘traditional’ bodily modification practices in Africa. This article takes issue with conventional representations of some African bodily modification practices as not only traditional but also disempowering. It draws on different and diverse accounts from urban middle class Shona women and men in Zimbabwe about ‘traditional’ practices of male circumcision and labia elongation. It also examines the different and complex connections people make between these gendered practices and issues of (sexual) desire, pleasure, and bodily aesthetics in relation to gendered identities. Based on my reflections of this research, the article demonstrates that the ways in which women and men make sense of their contemporary identities (in relation to these ‘traditional’ practices connected with sexuality) are embedded in a multiplicity of particular global and localised discourses on (anti)colonialism, religion, culture/tradition, modernity, and gender. In attempting to destabilise particular social categories, this article argues for the importance of engaging critically with people’s contradictory understandings and experiences of these practices in postcolonial African countries.